Predictive value of total CSVD burden scores in cognitive impairment among SLE patients on the basis of MRI evaluation - Lei Wang; Guimin Zheng; Xiuchuan Jia; Yingmin Chen (Advances in Rheumatology)
Abstract Background Cognitive impairment (CI) is a significant problem in systemic lupus erythematosus (SLE) patients. In recent years, total cerebral small vessel disease (CSVD) burden scores have had substantial value in predicting cognitive impairment. However, its application in treating concurrent cognitive impairment in SLE patients is unclear. To explore the relationship between total CSVD burden scores and cognitive dysfunction in SLE patients and to analyze its predictive value. Methods The Montreal Cognitive Assessment (MoCA) score was used to evaluate the cognitive function of 50 patients with SLE, and the total load score of patients with CSVD was analyzed via magnetic resonance imaging (MRI). Multivariate regression was used to evaluate the relationship between total CSVD burden scores and cognitive dysfunction, and the predictive value of total CSVD burden scores was assessed. Results Multivariate logistic regression analysis revealed that years of education (OR = 0.975, 95% CI [0.952–0.998], P = 0.035), neuropsychiatric systemic lupus erythematosus (NPSLE) (OR = 4.152, 95% CI [2.158–7.990], P < 0.001), and the CSVD total burden score (OR = 3.884, 95% CI [0.840–0.928], P < 0.001) were independently associated with cognitive impairment in SLE patients. The results of the ROC curve analysis revealed that the area under the curve (AUC) of the CSVD total burden score for the prediction of cognitive impairment in SLE patients was 0.885. Conclusions Years of education, NPSLE score, and total CSVD burden score are closely related to the occurrence of cognitive impairment in SLE patients. In particular, the total CSVD burden score is beneficial for the prediction of cognitive impairment. Clinical trial number Not applicable. Trial registration Not applicable.